2018
DOI: 10.2174/1874944501811010516
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Physical Activity in South Africa: Evidence from a National Population Based Survey

Abstract: Background: The health benefits of regular physical activity and exercise have been widely acknowledged. Yet physical inactivity remains an issue in South Africa. This study examines factors associated with physical activity amongst South Africans. Methods: This analysis used the 2012 nationally representative population-based household survey conducted using a multi-stage stratified cluster sampling design. Multinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 30 publications
4
26
4
Order By: Relevance
“…The most activities performed were of light intensity, as only a few of the pregnant women participate in moderate-to-vigorous intensity physical activity. This finding mirrors an earlier nationally representative population-based survey of 26,339 individuals, in which less than half of South Africans were moderately or vigorously physically active [52]. Our finding is consistent with other previous studies in South Africa [17,39], which reported 76.9% and 80.0% prevalence rates of household chores and walking, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…The most activities performed were of light intensity, as only a few of the pregnant women participate in moderate-to-vigorous intensity physical activity. This finding mirrors an earlier nationally representative population-based survey of 26,339 individuals, in which less than half of South Africans were moderately or vigorously physically active [52]. Our finding is consistent with other previous studies in South Africa [17,39], which reported 76.9% and 80.0% prevalence rates of household chores and walking, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to the explanation provided in another study [16], the explanatory variables used were sociodemographic and behavioural factors. For characterisation of socio-demographics, age was grouped into two categories namely: 15 to 19 years and 20 to 24 years.…”
Section: Explanatory Variablesmentioning
confidence: 99%
“…Few studies have focused on PA in older adults in LMICs, and fewer still have focused on South Africa. Reported levels of South African adults’ PA has ranged between 31.0% of adults older than 50 years being ‘physically active’ (defined in the paper as being moderately or vigorously active, based on two adapted questions in a national survey) [ 7 ] to 50% meeting PA guidelines (defined as doing >150 min/week of moderate- to vigorous-intensity PA), based on a limited sample of adults aged above 60 years in care homes [ 8 ]. One small pilot study conducted in South Africa found that the socioeconomic status, traffic, and features of the built environment were associated with objectively measured PA levels in older people [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…One small pilot study conducted in South Africa found that the socioeconomic status, traffic, and features of the built environment were associated with objectively measured PA levels in older people [ 9 ]. Three studies have examined rural adult populations in South Africa to date, the first of which enrolled young to middle-aged adults [ 10 ], the second specified ‘community-dwelling’ older adults, but included both urban and rural adults over 50 [ 11 ], and the third included participants aged from 18 years [ 7 ]. Correlates of not meeting PA guidelines in older adults include pain, slow gait, and low grip strength [ 11 ]; while in the national survey study, physical inactivity was higher in individuals aged above 50 years, female, with at least one chronic medical condition and from rural settlements [ 7 ].…”
Section: Introductionmentioning
confidence: 99%